Combining Biologics Targeting Eosinophils (IL-5/IL-5R), IgE, and IL-4/IL-13 in Allergic and Inflammatory Diseases - Mitchell M. Pitlick, MD; Thanai Pongdee, MD (World Allergy Organization Journal, 2022)
The indications for biologic therapy are expanding. Patients may benefit from different biologics for separate conditions or one condition with multiple pathogenic mechanisms targeted by different biologics. We sought to determine the frequency and safety of combining biologics targeting IgE, IL-5, IL-5R, and IL-4/IL-13 in patients referred to a large academic health system through retrospective chart review. Between January 1, 2015 and July 31, 2021, 25 patients receiving multiple biologics simultaneously were identified. Combinations included omalizumab + mepolizumab (n = 11), omalizumab + dupilumab (n = 6), omalizumab + benralizumab (n = 4), mepolizumab + dupilumab (n = 3), and omalizumab + dupilumab + mepolizumab (n = 1). Sixteen patients were receiving multiple biologics for the same condition, most commonly asthma (n = 10). Nine patients were treated for separate conditions, with chronic spontaneous urticaria and atopic dermatitis being the most common combination (n = 3). The median duration of combination biologic use was 17.5 months. There were no reports of anaphylaxis, other allergic reaction, immune dysfunction, pneumonia, or development of malignancy. The use of multiple biologics appears to be well tolerated in this case series. Prospective study is needed to better determine the efficacy, safety, and cost-effectiveness of this approach.